2010
DOI: 10.1007/s00213-010-1809-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoking produces rapid rise of [11C]nicotine in human brain

Abstract: Uptake in human brain from a single inhalation was sufficiently rapid that it is plausible that fast rate-of-rise contributes to nicotine dependence in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 51 publications
4
65
0
Order By: Relevance
“…47,48 These data are consistent with a large body of evidence suggesting that rapid delivery of drugs leads to increased addictive symptomatology than slower delivery. [49][50][51] However, e-cigarettes are likely to evolve into more rapid nicotine delivery systems as product design is improved, as we have already seen in comparisons between first and second generation e-cigarettes. 47,52 E-cigarettes were further rated as less likely to cause a negative social impression and as more similar to cigarettes than NRT in enhancing social experiences.…”
Section: E-cigarettes Versus Cigarettesmentioning
confidence: 99%
“…47,48 These data are consistent with a large body of evidence suggesting that rapid delivery of drugs leads to increased addictive symptomatology than slower delivery. [49][50][51] However, e-cigarettes are likely to evolve into more rapid nicotine delivery systems as product design is improved, as we have already seen in comparisons between first and second generation e-cigarettes. 47,52 E-cigarettes were further rated as less likely to cause a negative social impression and as more similar to cigarettes than NRT in enhancing social experiences.…”
Section: E-cigarettes Versus Cigarettesmentioning
confidence: 99%
“…Adding NH 4 Cl to the perfusate affects the pH i of cells by releasing freely diffusible NH 3 (Fig. 3b).…”
Section: Intracellular Phmentioning
confidence: 99%
“…The rapid transport of nicotine from the blood to the brain seems to be critical for its neurobiological effects (1,3). A positron emission tomography study of human subjects showed that the nicotine concentration in the brain reached 50% of its maximum within 15 s, illustrating how a rapid rise contributes to nicotine dependence in smokers (4). Nicotine must cross the blood-brain barrier (BBB) to reach the brain parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the goal of NRT is to slowly cutback on nicotine levels until cessation. This is different from when an individual administers nicotine through inhalation which reaches the brain in around 15 seconds and is metabolised quickly causing spikes in nicotine blood levels (35).…”
Section: Nicotine Replacement Therapymentioning
confidence: 91%